Metric suite to Evaluate Reusability of Software Product Line - Mohammad Ali Torkamani (International Journal of Electrical and Computer Engineering (IJECE), 2014)
Metrics have long been used to measure and evaluate  software products and processes. Software product line architecture is a field in which few metrics have been applied, a surprising fact given the important role of software product line architecture in software product line development. Recently, Some metrics have been developed to assess software product line architecture. These metrics are useful but have not been widely used in industry. In this paper, some new metrics are provided to assess reusability of Software product line architecture. Our metrics are evaluated in action.DOI:http://dx.doi.org/10.11591/ijece.v4i2.5137